Collaborative relationships between logistics service providers and humanitarian organizations during disaster relief operations - Jennifer Bealt; Jair Camilo Fernández Barrera; S. Afshin Mansouri (Journal of Humanitarian Logistics and Supply Chain Management)
Purpose – – The purpose of this paper is to explore barriers and benefits of establishing relationships between humanitarian organizations (HOs) and logistics service providers (LSPs) in order to improve humanitarian disaster relief operations (DROs). The perceptions of a variety of actors are explored to determine key factors which influence collaboration. Design/methodology/approach – – This study comprises of qualitative and quantitative methodological approaches. A comprehensive literature review was undertaken alongside an online survey with a variety of respondents. Descriptive statistics, data visualization and qualitative data analysis were implemented to analyse survey results. A follow-up survey and interviews with LSPs validated the results. Findings – – The research presents the opinions of a variety of actors involved in DROs and reveals barriers which affect HO/LSP collaboration. Explanations for these barriers and possible solutions to mitigate them are disclosed. The findings also uncover gaps between research and practice; providing new insights into behaviour in the humanitarian field. Practical implications – – The authors provide an in-depth understanding of the barriers and challenges faced in this field and suggest a reevaluation of corporate decision making in order to increase trust between LSPs and HOs. The authors identify future research topics including the impact of donors and military organizations on HO decision making, and analysis of variables which may affect the formation of collaborative partnerships. Originality/value – – The authors introduce a unique empirical insight into the perspectives of HOs, LSPs and academics and offers suggestions for mitigating the numerous barriers associated with successful collaborative partnerships between HOs and LSPs.